De novo European eel transcriptome provides insights into the evolutionary history of duplicated genes in teleost lineages. - Christoffer Rozenfeld; Jose Blanca; Victor Gallego; Víctor García-Carpintero; Juan Germán Herranz-Jusdado; Luz Pérez; Juan F Asturiano; Joaquín Cañizares; David S Peñaranda (PLoS ONE, 2019)
Paralogues pairs are more frequently observed in eels (Anguilla sp.) than in other teleosts. The paralogues often show low phylogenetic distances; however, they have been assigned to the third round of whole genome duplication (WGD), shared by all teleosts (3R), due to their conserved synteny. The apparent contradiction of low phylogenetic difference and 3R conserved synteny led us to study the duplicated gene complement of the freshwater eels. With this aim, we assembled de novo transcriptomes of two highly relevant freshwater eel species: The European (Anguilla anguilla) and the Japanese eel (Anguilla japonica). The duplicated gene complement was analysed in these transcriptomes, and in the genomes and transcriptomes of other Actinopterygii species. The study included an assessment of neutral genetic divergence (4dTv), synteny, and the phylogenetic origins and relationships of the duplicated gene complements. The analyses indicated a high accumulation of duplications (1217 paralogue pairs) among freshwater eel genes, which may have originated in a WGD event after the Elopomorpha lineage diverged from the remaining teleosts, and thus not at the 3R. However, very similar results were observed in the basal Osteoglossomorpha and Clupeocephala branches, indicating that the specific genomic regions of these paralogues may still have been under tetrasomic inheritance at the split of the teleost lineages. Therefore, two potential hypotheses may explain the results: i) The freshwater eel lineage experienced an additional WGD to 3R, and ii) Some duplicated genomic regions experienced lineage specific rediploidization after 3R in the ancestor to freshwater eels. The supporting/opposing evidence for both hypotheses is discussed.